Shopping on the go: how walking influences mobile shopping performance. (2018) - Stanley, Sarah M.; Elrod, Cassandra C.; Twyman, Nathan W.; Zou, Cui
Given the growth in use and capabilities of mobile devices, the mobile commerce (m-commerce) market is also continuing to grow and become more sophisticated. Studies exploring the results of m-commerce using mobile devices, however, have traditionally been done in a stationary setting. This exploratory study seeks to examine how m-commerce is impacted by the use of mobile devices in a stationary versus a walking setting. Treadmill desks were used to replicate mobile shopping while using mobile devices and then compared the results with the same task completed on mobile devices in a stationary manner. Results indicate that shopping while walking increases the time it takes to complete the shopping task but not the dollar amount spent for the product in question.